A highly wear-resistant halogen-free radiation cross-linked sheath material and preparation method thereof
By using ethylene-ethyl acetate co-polymers and other raw materials, combined with the process of dense refiners and double screw extrusion machines to prepare high-tear-resistant halogen-free radicals, solving the halogen-free sprays The problem of poor wear resistance in the material has achieved excellent abrasion resistance, flame retardant and mechanical properties.
Patent Information
- Application Number
- CN202410639814.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-22
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-05-22
AI Technical Summary
Halogen-free irradiated crosslinked sheath materials have poor wear resistance and are difficult to meet the needs of cables such as automotive wiring harnesses that require high wear resistance.
Ethylene-ethyl acetate, ethyl acetate, polyethylene polyethylene, polyethylene clotteric anhydride, aluminum hydroxide, and modified graphene, etc. The process of building grains and radiation cross -linking, prepare high -abrasion -resistant halogen -free irradiated federations.
It significantly improves the abrasion resistance, flame retardant performance and mechanical performance of the protective cover material. At the same time, it reduces the addition and improves the flame retardant effect of aluminum hydroxide. The material stability is high and the cost economy.
Smart Images

Figure BDA0004852959660000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cable sheath materials, and in particular relates to a highly wear-resistant halogen-free radiation cross-linked sheath material and a preparation method thereof. Background Art
[0002] In today's increasingly developed industrialized society, energy and information are the two pillars of society. Whether it is the transmission of electricity or information, it is inseparable from wires and cables, especially large-scale commercial and entertainment centers, subways, tunnels and nuclear power plants. Although ordinary polyvinyl chloride insulated wires and cables have excellent mechanical, electrical and processing properties, they still have defects such as high calorific value and release of a large amount of toxic and harmful corrosive gases and thick smoke when burned. This has prompted the global focus of the wire and cable industry on the development of halogen-free and low-smoke products. However, under the premise of ensuring that the wires and cables have excellent flame retardant properties, flame retardants are usually required to be highly filled, resulting in poor appearance and poor wear resistance of the wires and cables. This is undoubtedly a difficult problem that needs to be solved urgently for cables such as automotive wiring harnesses that require high wear resistance. Summary of the invention
[0003] The object of the present invention is to provide a highly wear-resistant halogen-free radiation cross-linked sheath material and a preparation method thereof, so as to solve the problem of poor wear resistance in the halogen-free radiation cross-linked sheath material.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A highly wear-resistant halogen-free radiation cross-linked sheath material, comprising the following raw materials in parts by weight:
[0006] 30-50 parts of ethylene-vinyl acetate copolymer;
[0007] Ultra high molecular weight polyethylene 5-10 parts;
[0008] Polyethylene grafted maleic anhydride 1-5 parts;
[0009] 40-60 parts of modified aluminum hydroxide;
[0010] 6-10 parts of modified graphene;
[0011] Antioxidant 0.5-1 part;
[0012] Lubricant 0.8-2.0 parts;
[0013] The modified graphene is prepared by the following steps:
[0014] Graphene oxide, silane coupling agent KH-550 and coconut oil fatty acid diethanolamide are added to acetone, ultrasonically dispersed, palm fiber is added, stirring is continued, filtering is performed, and drying is performed to obtain modified graphene.
[0015] Preferably, the usage ratio of graphene oxide, silane coupling agent KH-550, coconut oil fatty acid diethanolamide, acetone and palm fiber is 9-10g:3.5g:0.85-1g:50mL:28-30g.
[0016] Preferably, the graphene oxide is prepared by the Hummers method.
[0017] Preferably, the modified aluminum hydroxide is prepared by the following steps:
[0018] Aluminum hydroxide and deionized water are added to anhydrous ethanol and stirred to obtain a mixed solution; phytic acid and silane coupling agent KH-550 are mixed and added to the mixed solution, the temperature is raised to 60° C., stirred, filtered, washed, centrifuged, and dried to constant weight to obtain modified aluminum hydroxide.
[0019] Preferably, the dosage ratio of aluminum hydroxide, deionized water, anhydrous ethanol, phytic acid and silane coupling agent KH-550 is 10g:10mL:90mL:5-6mL:0.5-0.6g.
[0020] Preferably, the molecular weight of the high molecular weight polyethylene is 3 million to 6 million.
[0021] Preferably, the antioxidant is one or both of the antioxidant 1010 and the antioxidant 168.
[0022] Preferably, the lubricant is one or more of zinc stearate, calcium stearate, barium stearate or polyethylene wax.
[0023] The present invention also provides a method for preparing a highly wear-resistant halogen-free radiation cross-linked sheath material, comprising the following steps:
[0024] The components are weighed in parts by weight, added into an internal mixer for melt blending, and then sequentially extruded and granulated through a twin-screw extruder, and irradiated and cross-linked to obtain a highly wear-resistant halogen-free irradiation-cross-linked sheath material.
[0025] Preferably, the mixing temperature is 150-180°C, and the mixing time is 8-14 minutes; the first zone of the twin-screw extruder is 95-110°C, the second zone is 110-125°C, the third zone is 130-140°C, the fourth zone is 130-140°C, the fifth zone is 125-130°C, and the sixth zone is 110-120°C.
[0026] Beneficial effects of the present invention:
[0027] The present invention first performs oxidation treatment on graphite to activate the graphite surface to obtain graphene oxide, and then uses palm fiber to perform surface modification on the graphene oxide surface to obtain modified graphene, so as to improve the interface compatibility and dispersion uniformity between graphite and base material. Graphene with a lamellar structure can easily promote the material to form a smooth lubricating film on the opposite surface during the friction process, thereby achieving a good lubricating effect. In addition, the surface-grafted palm fiber has the characteristics of high strength and high toughness. When added to the raw material to obtain the sheath material, the wear resistance of the sheath material is significantly improved, and the mechanical properties of the material are also improved to a certain extent.
[0028] In order to further reduce the addition amount and improve the flame retardant effect of aluminum hydroxide in the sheath material, the present invention grafts phytic acid onto the surface of aluminum hydroxide through a silane coupling agent to obtain phytic acid-coated aluminum hydroxide. On the one hand, after the phytic acid coating, the compatibility of the aluminum hydroxide flame retardant and the substrate is increased, thereby improving the mechanical strength of the sheath material; on the other hand, the phytic acid decomposes at high temperature to generate small molecules such as phosphoric acid or polyphosphoric acid, which can capture flammable free radicals, and after the phytic acid is burned, a circular structure is formed and attached to the surface of the aluminum hydroxide, making it more difficult to release smoke and toxic gases, while blocking the dissipation and propagation of heat, thereby improving the flame retardant performance of the sheath material.
[0029] The preparation method of the present invention is simple, easy to operate, and the composition of the raw materials is reasonable, which is convenient for industrial production. The addition of modified graphene and modified aluminum hydroxide makes the compatibility between the formula materials good, and improves the wear resistance and flame retardancy of the sheath material. The highly wear-resistant halogen-free radiation cross-linked sheath material prepared by the present invention has excellent wear resistance, flame retardancy and mechanical properties, high stability and economical cost. DETAILED DESCRIPTION
[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] The graphene oxide used in the embodiments and comparative examples of the present invention is prepared by the Hummers method, and the specific steps are as follows:
[0032] 0.3 g of graphene was added to 2.4 mL of concentrated sulfuric acid, and after stirring for 0.5 h, 0.5 g of sodium nitrate was added, the temperature was raised to 80 ° C, and stirring was continued for 5 h. 12 mL of concentrated sulfuric acid was added, and the reaction temperature was controlled to be less than 3 ° C. After slowly adding 1.5 g of potassium permanganate, the temperature was raised to 35 ° C, and stirring was continued for 2.5 h. Then 70 mL of deionized water and 2 mL of H2O2 (mass fraction of 30%) were added, centrifuged, and washed with 5% HCl and deionized water in turn to pH 7. Finally, it was dried at 60 ° C for 65 h to obtain graphene oxide.
[0033] Example 1
[0034] This embodiment provides a modified graphene, and the preparation steps are as follows:
[0035] 9 g of graphene oxide, 3.5 g of silane coupling agent KH-550 and 0.85 g of coconut oil fatty acid diethanolamide were added to 50 mL of acetone, ultrasonically dispersed for 1 h, 30 g of palm fiber was added, stirring was continued for 1.5 h, filtered, and dried in an oven at 85 ° C for 3 h to obtain modified graphene.
[0036] Example 2
[0037] This embodiment provides a modified graphene, and the preparation steps are as follows:
[0038] 10 g of graphene oxide, 3.5 g of silane coupling agent KH-550 and 1 g of coconut oil fatty acid diethanolamide were added to 50 mL of acetone, ultrasonically dispersed for 1 h, 30 g of palm fiber was added, stirring was continued for 2 h, filtered, and dried in an oven at 85 ° C for 3 h to obtain modified graphene.
[0039] Comparative Example 1
[0040] The modified graphene of this comparative example is the graphene oxide prepared in the present invention.
[0041] Example 3
[0042] This embodiment provides a modified aluminum hydroxide, and the preparation steps are as follows:
[0043] Add 10 g of aluminum hydroxide and 10 mL of deionized water to 90 mL of anhydrous ethanol and stir to obtain a mixed solution; mix 5 mL of phytic acid and 0.5 g of silane coupling agent KH-550 evenly and add them to the mixed solution, heat to 60°C and stir for 3 hours, filter, wash with anhydrous ethanol 5 times, centrifuge, and dry at 70°C to constant weight to obtain modified aluminum hydroxide.
[0044] Example 4
[0045] This embodiment provides a modified aluminum hydroxide, and the preparation steps are as follows:
[0046] Add 10 g of aluminum hydroxide and 10 mL of deionized water to 90 mL of anhydrous ethanol and stir to obtain a mixed solution; mix 6 mL of phytic acid and 0.55 g of silane coupling agent KH-550 evenly and add them to the mixed solution, heat to 60 ° C and react with stirring for 3 hours, filter, wash with anhydrous ethanol 5 times, centrifuge, and dry at 70 ° C to constant weight to obtain modified aluminum hydroxide.
[0047] Comparative Example 2
[0048] This comparative example provides a modified aluminum hydroxide, and the preparation steps are as follows:
[0049] 10 g of aluminum hydroxide and 10 mL of deionized water were added to 90 mL of anhydrous ethanol, stirred, filtered, washed with anhydrous ethanol for 5 times, centrifuged, and dried at 70° C. to constant weight to obtain modified aluminum hydroxide.
[0050] Example 5
[0051] This embodiment provides a highly wear-resistant halogen-free radiation cross-linked sheath material, comprising the following raw materials in parts by weight:
[0052] 35 parts of ethylene-vinyl acetate copolymer, 5 parts of ultra-high molecular weight polyethylene (molecular weight of 3 million), 3 parts of polyethylene grafted maleic anhydride, 46 parts of modified aluminum hydroxide in Example 3, 6 parts of modified graphene in Example 1, 0.5 parts of antioxidant 1010, and 0.8 parts of zinc stearate.
[0053] The preparation steps are as follows:
[0054] Ethylene-vinyl acetate copolymer, ultra-high molecular weight polyethylene, polyethylene grafted maleic anhydride, modified aluminum hydroxide, modified graphene, antioxidant and lubricant are weighed by weight, and each component is added into an internal mixer for melt blending, the internal mixing temperature is 150° C., and the internal mixing time is 10 minutes; then, granulation is performed by extrusion through a twin-screw extruder in sequence, wherein the first zone of the twin-screw extruder is 95° C., the second zone is 110° C., the third zone is 130° C., the fourth zone is 130° C., the fifth zone is 125° C., and the sixth zone is 110° C.; radiation cross-linking is performed to obtain a highly wear-resistant halogen-free radiation cross-linked sheath material.
[0055] Example 6
[0056] The only difference from Example 5 is that:
[0057] 45 parts of ethylene-vinyl acetate copolymer, 8 parts of ultra-high molecular weight polyethylene (molecular weight of 3 million), 3 parts of polyethylene grafted maleic anhydride, 50 parts of modified aluminum hydroxide in Example 3, 8 parts of modified graphene in Example 2, 1680.5 parts of antioxidant, and 0.8 parts of zinc stearate.
[0058] The remaining materials and steps are the same as those in Example 5.
[0059] Example 7
[0060] The only difference from Example 5 is that:
[0061] 50 parts of ethylene-vinyl acetate copolymer, 10 parts of ultra-high molecular weight polyethylene (molecular weight of 6 million), 3 parts of polyethylene grafted maleic anhydride, 60 parts of modified aluminum hydroxide in Example 4, 10 parts of modified graphene in Example 2, 0.5 parts of antioxidant 1010, and 0.8 parts of polyethylene wax.
[0062] The remaining materials and steps are the same as those in Example 5.
[0063] Example 8
[0064] The only difference from Example 7 is that the preparation steps are different:
[0065] Ethylene-vinyl acetate copolymer, ultra-high molecular weight polyethylene, polyethylene grafted maleic anhydride, modified aluminum hydroxide, modified graphene, antioxidant and lubricant are weighed by weight, and each component is added into an internal mixer for melt blending, the internal mixing temperature is 175° C., and the internal mixing time is 12 minutes; then, granulation is performed by extrusion through a twin-screw extruder in sequence, wherein the first zone of the twin-screw extruder is 100° C., the second zone is 115° C., the third zone is 135° C., the fourth zone is 135° C., the fifth zone is 125° C., and the sixth zone is 110° C.; radiation cross-linking is performed to obtain a highly wear-resistant halogen-free radiation cross-linked sheath material.
[0066] The remaining materials and steps are the same as those in Example 7.
[0067] Comparative Example 3
[0068] The only difference from Example 5 is that:
[0069] The modified graphene in Example 1 was replaced by the modified graphene in Comparative Example 1, and the remaining raw materials and steps were the same as those in Example 5.
[0070] Comparative Example 4
[0071] The only difference from Example 5 is that:
[0072] The 6 parts of modified graphene in Example 1 were replaced by 3 parts of modified graphene in Comparative Example 1, and the remaining raw materials and steps were the same as those in Example 5.
[0073] Comparative Example 5
[0074] The only difference from Example 6 is that:
[0075] The modified aluminum hydroxide in Example 3 is replaced by the modified aluminum hydroxide in Comparative Example 2, and the remaining raw materials and steps are the same as those in Example 6.
[0076] Comparative Example 6
[0077] The only difference from Example 7 is that the preparation steps are different:
[0078] Ethylene-vinyl acetate copolymer, ultra-high molecular weight polyethylene, polyethylene grafted maleic anhydride, modified aluminum hydroxide, modified graphene, antioxidant and lubricant are weighed by weight, and each component is added into an internal mixer for melt blending, the internal mixing temperature is 140° C., and the internal mixing time is 8 minutes; then, granulation is performed by extrusion through a twin-screw extruder in sequence, wherein the first zone of the twin-screw extruder is 90° C., the second zone is 100° C., the third zone is 120° C., the fourth zone is 125° C., the fifth zone is 115° C., and the sixth zone is 100° C.; radiation cross-linking is performed to obtain a highly wear-resistant halogen-free radiation cross-linked sheath material.
[0079] The following performance tests were performed on Examples 5 to 8 and Comparative Examples 3 to 6:
[0080] 1) Tensile strength test: The tensile properties of the cable material are tested in accordance with standard GB / T1040.3-2006.
[0081] 2) Elongation at break test: The tensile properties of the cable material are tested in accordance with standard GB / T1040.3-2006.
[0082] 3) Oxygen index test: According to standard GB / T 2406.3-2022, the cable material is subjected to a high temperature test to determine its oxygen index.
[0083] 4) According to the standard GB / T 9867-2008 "Determination of wear resistance of vulcanized rubber or thermoplastic rubber (rotating roller abrader method)", the relative volume wear of the highly wear-resistant halogen-free radiation cross-linked sheath materials prepared in the examples and comparative examples was tested respectively.
[0084] The results are shown in Table 1:
[0085] Table 1
[0086]
[0087] It can be seen from Table 1 that the tensile strength of the highly wear-resistant halogen-free radiation cross-linked sheath material prepared by the present invention is above 19.5MPa, the elongation at break is above 426%, the oxygen index is above 35%, and the relative volume wear is less than 32mm 3 It can be seen that the high wear-resistant halogen-free radiation cross-linked sheath material provided by the present invention has excellent mechanical properties, flame retardant properties and wear resistance.
[0088] Compared with Example 5, Comparative Example 3 adds the graphene oxide in Example 1, and Example 5 adds the modified graphene in Example 1. The relative volume wear of the highly wear-resistant halogen-free radiation cross-linked sheath material obtained in Example 5 is lower than that in Comparative Example 3, indicating that after modifying the graphene oxide with palm fiber, the compatibility of graphene and the sheath material can be improved, thereby improving the wear resistance of the graphene.
[0089] Compared with Example 5, Comparative Example 4 contains 3 parts of modified graphene, while Example 5 contains 6 parts of modified graphene. The tensile strength, elongation at break and oxygen index of Example 5 are all higher than those of Comparative Example 4, and the relative volume abrasion loss is lower than that of Comparative Example 4, indicating that the amount of modified graphene used will also affect the mechanical properties, flame retardant properties and wear resistance of the sheath material.
[0090] Compared with Example 6, Comparative Example 5 adds the modified aluminum hydroxide in Example 2, while Example 5 adds the modified aluminum hydroxide in Example 3. The oxygen index of the highly wear-resistant halogen-free radiation cross-linked sheath material obtained in Example 6 is higher than that of Comparative Example 5, indicating that the compatibility of the flame retardant and the substrate is increased after the aluminum hydroxide is coated with phytic acid. At the same time, the phosphorus in the aluminum hydroxide and phytic acid exerts synergistic flame retardant properties, which greatly improves the flame retardant properties of the sheath material.
[0091] Compared with Example 7, the preparation process of the highly wear-resistant halogen-free radiation cross-linked sheath material prepared in Example 6 is different from that in Example 7. The tensile strength, elongation at break and oxygen index in Example 7 are all higher than those in Example 6, and the relative volume abrasion is lower than that in Example 6, indicating that the preparation process will also affect the mechanical properties, flame retardant properties and wear resistance of the sheath material.
[0092] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0093] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A highly wear-resistant halogen-free radiation cross-linked sheath material, characterized in that: By weight, it includes the following raw materials: 30-50 parts of ethylene-vinyl acetate copolymer; Ultra high molecular weight polyethylene 5-10 parts; Polyethylene grafted maleic anhydride 1-5 parts; 40-60 parts of modified aluminum hydroxide; 6-10 parts of modified graphene; Antioxidant 0.5-1 part; Lubricant 0.8-2.0 parts; The modified graphene is prepared by the following steps: Graphene oxide, silane coupling agent KH-550 and coconut oil fatty acid diethanolamide are added to acetone, ultrasonically dispersed, palm fiber is added, stirring is continued, filtering is performed, and drying is performed to obtain modified graphene; Modified aluminum hydroxide is prepared by the following steps: Aluminum hydroxide and deionized water are added to anhydrous ethanol, stirred to obtain a mixed solution; phytic acid and silane coupling agent KH-550 are mixed and added to the mixed solution, the mixture is heated to 60° C., stirred, filtered, washed, centrifuged, and dried to constant weight to obtain modified aluminum hydroxide; The method for preparing the highly wear-resistant halogen-free radiation cross-linked sheath material comprises the following steps: Weigh each component by weight, add each component into an internal mixer for melt blending, and then extrude and granulate through a twin-screw extruder in sequence, and irradiate and cross-link to obtain a highly wear-resistant halogen-free irradiation cross-linked sheath material; Among them, the mixing temperature is 150-180℃, and the mixing time is 8-14 minutes; the first zone of the twin-screw extruder is 95-110℃, the second zone is 110-125℃, the third zone is 130-140℃, the fourth zone is 130-140℃, the fifth zone is 125-130℃, and the sixth zone is 110-120℃.
2. The highly wear-resistant halogen-free radiation cross-linked sheath material according to claim 1, characterized in that: The usage ratio of graphene oxide, silane coupling agent KH-550, coconut oil fatty acid diethanolamide, acetone and palm fiber is 9-10g:3.5g:0.85-1g:50mL:28-30g.
3. The highly wear-resistant halogen-free radiation cross-linked sheath material according to claim 1, characterized in that: The graphene oxide is prepared by the Hummers method.
4. The highly wear-resistant halogen-free radiation cross-linked sheath material according to claim 1, characterized in that: The dosage ratio of aluminum hydroxide, deionized water, anhydrous ethanol, phytic acid and silane coupling agent KH-550 is 10g:10mL:90mL:5-6mL:0.5-0.6g.
5. The highly wear-resistant halogen-free radiation cross-linked sheath material according to claim 1, characterized in that: The molecular weight of high molecular weight polyethylene is 3 million to 6 million.
6. The highly wear-resistant halogen-free radiation cross-linked sheath material according to claim 1, characterized in that: The antioxidant is one or both of the antioxidant 1010 and the antioxidant 168.
7. The highly wear-resistant halogen-free radiation cross-linked sheath material according to claim 1, characterized in that: The lubricant is one or more of zinc stearate, calcium stearate, barium stearate or polyethylene wax.
Citation Information
Patent Citations
Halogen-free flame-retardant synergistic functional masterbatch special for styrene resin modification and preparation method thereof
CN110615936A
Outdoor anti-aging cable material and preparation method thereof
CN116144098A